Click to Buy: The Impact of Brand Image and Visual Appeal on Online Consumer Behavior - Setiarini, Mersiana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2025)
The rapid development of e-commerce has encouraged companies to build stronger branding strategies to attract the attention of digital consumers. In this context, brand image and brand visual appeal are two important elements that influence online purchasing decisions. This study aims to analyze the influence of brand image and brand visual appeal on consumer purchasing decisions on e-commerce applications. Quantitative methods are used in this study by collecting data through surveys of active users of e-commerce platforms. The results of the analysis show that both brand image and brand visual appeal have a positive and significant effect on online purchasing decisions. This finding indicates that positive perceptions of brand image and attractive visual appearance can increase consumer interest in making purchases. This study provides strategic implications for e-commerce business actors to consistently build a strong brand image and pay attention to visual aspects in product design and presentation on digital platforms.